2021
DOI: 10.1093/mnras/stab2059
|View full text |Cite
|
Sign up to set email alerts
|

Planetary migration in precessing discs for S-type wide binaries

Abstract: The discovery of numerous circumprimary planets in the last few years has brought to the fore the question of planet formation in binary systems. The significant dynamical influence, during the protoplanetary disk phase, of a binary companion on a giant planet has previously been highlighted for wide binary stars. In particular, highly inclined binary companion can induce perturbations on the disk and the planets, through the Lidov-Kozai resonance, which could inhibit the formation process. In this work, we ai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Using a symplectic N-body integrator designed for binary star systems, in which the dissipation for the planet due to the disc is implemented following the formulas of Bitsch et al (2013), Roisin and Libert (2021) noted that accumulations of the pericenter arguments around 90 • and 270 • are clearly visible at the dispersal of the disc (left panel of Fig. 7).…”
Section: Planets In Binary Star Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a symplectic N-body integrator designed for binary star systems, in which the dissipation for the planet due to the disc is implemented following the formulas of Bitsch et al (2013), Roisin and Libert (2021) noted that accumulations of the pericenter arguments around 90 • and 270 • are clearly visible at the dispersal of the disc (left panel of Fig. 7).…”
Section: Planets In Binary Star Systemsmentioning
confidence: 99%
“…This reflects the significant dynamical influence of a wide binary 60 A.-S. Libert companion (here at 1000 AU) on the evolution of a giant planet during its migration in the protoplanetary disc. However, when considering additional effects related to the disc, such as the disc gravitational potential acting on the planet (e.g., Terquem and Ajmia 2010;Teyssandier et al 2013) and the nodal precession induced by the binary companion on the disc (e.g., Batygin et al 2011;Zanazzi and Lai 2018), Roisin et al (2021) showed that accumulations disappear (right panel of Fig. 7).…”
Section: Planets In Binary Star Systemsmentioning
confidence: 99%
See 1 more Smart Citation